Genetic epidemiology of rheumatoid arthritis. - Lynn, A H (1995)
We conducted family studies and segregation analyses of rheumatoid arthritis (RA) that were based on consecutive patients with RA ascertained without regard to family history or known risk factors. First-degree relatives from 135 simplex and 30 multiplex families were included in the analyses. A highly penetrant recessive major gene, with a mutant allele frequency of .005, was identified as the most parsimonious genetic risk factor. Significant evidence for heterogeneity in risk for RA was observed for proband gender but not for proband age at onset. Kaplan-Meier risk analysis demonstrated significant evidence for differences in the distribution of risk among first-degree relatives. These analyses demonstrated that both proband gender and age at onset are important risk factors but that proband gender appears to be the more important determinant of risk, with relatives of male probands having the greatest cumulative risk for RA. In addition, log-linear modeling identified proband gender, familiality (multiplex or simplex), and an interaction term between these two variables as being adequate to define the distribution of risk in families. The pattern of risk for RA among susceptible individuals and its inheritance is thus heterogeneous. For future genetic analyses, families with an excess of affected males having a young age at onset may be the most informative in identifying the putative recessive gene and its modifiers.